Business of the heart : religion and emotion in the nineteenth century - Corrigan, John, 1952- (University of California Press, 2002)
The 'Businessmen's Revival' was a religious revival that unfolded in the wake of the 1857 market crash among white, middle-class Protestants. Delving into the religious history of Boston in the 1850s, John Corrigan gives an imaginative and wide-ranging interpretive study of the revival's significance.
Keywords: Revivals -- Massachusetts -- Boston -- History -- 19th century.; Emotions -- Religious aspects -- Christianity -- History of doctrines -- 19th century.; Protestants -- Massachusetts -- Boston -- History -- 19th century.; Businessmen -- Religious life -- Massachusetts -- Boston.; Réveils (Religion) -- Massachusetts -- Boston -- Histoire -- 19e siècle.; Émotions -- Aspect religieux -- Christianisme -- Histoire des doctrines -- 19e siècle.; Protestants -- Massachusetts -- Boston -- Histoire -- 19e siècle.; Hommes d'affaires -- Massachusetts -- Boston -- Vie religieuse.; RELIGION -- Christianity -- History.; RELIGION / Christianity / General; Businessmen -- Religious life; Emotions -- Religious aspects -- Christianity -- History of doctrines; Protestants; Revivals; Massachusetts -- Boston; Opwekkingsbewegingen.; Massachusetts.; 1800-1899; History